Factors Related to Utilization of Maternal Child Health Handbook Data by Midwives (Unnes Journal of Public Health, 2021)
Midwives are one of the health workers utilizing the MCH (Maternal Child Health) handbook which records the data used to prevent infant, under-five, and maternal mortality. This study aimed to investigate factors related to utilization of the MCH handbook data, namely individual, organizational, and operational techniques. Quantitative approach was used in a cross-sectional survey with a structured questionnaire. Thirty-one midwives were selected as the sample from Active Alert Village in Temanggung district with rural and urban area representative consideration. Besides, descriptive data were tabulated, and inferential analysis was conducted by Pearson product-moment correlation. Result showed the rate of MCH Handbook data utilization was 78.54%. Also, data requirement perception, data filling skill, motivation, attitudes of midwives and facilities availablity (p < 0.05) are significantly related. The MCH handbook data utilization was determined by the individual factor, but with no significant relationship to operational and organizational factors except facilities availability. Therefore, efforts are required to improve data utilization by increasing data requirement perception, data filling skills, motivation and midwives attitudes.